Accuracy of Stereovision-Updated Versus Preoperative CT-Based Image Guidance in Multilevel Lumbar Pedicle Screw Placement: A Cadaveric Swine Study. Issue 1 (January 2022) - Fan, Xiaoyao; Mirza, Sohail K.; Li, Chen; Evans, Linton T.; Ji, Songbai; Paulsen, Keith D.
Abstract : Background: Change in vertebral position between preoperative imaging and the surgical procedure reduces the accuracy of image-guided spinal surgery, requiring repeated imaging and surgical field registration, a process that takes time and exposes patients to additional radiation. We developed a handheld, camera-based, deformable registration system (intraoperative stereovision, iSV) to register the surgical field automatically and compensate for spinal motion during surgery without further radiation exposure. Methods: We measured motion-induced errors in image-guided lumbar pedicle screw placement in 6 whole-pig cadavers using state-of-the-art commercial spine navigation (StealthStation; Medtronic) and iSV registration that compensates for intraoperative vertebral motion. We induced spinal motion by using preoperative computed tomography (pCT) of the lumbar spine performed in the supine position with accentuated lordosis and performing surgery with the animal in the prone position. StealthStation registration of pCT occurred using metallic fiducial markers implanted in each vertebra, and iSV data were acquired to perform a deformable registration between pCT and the surgical field. Sixty-eight pedicle screws were placed in 6 whole-pig cadavers using iSV and StealthStation registrations in random order of vertebral level, relying only on image guidance without invoking the surgeon's judgment. The position of each pedicle screw was assessed with post-procedure CT and confirmed via anatomical dissection. Registration errors were assessed on the basis of implanted fiducials. Results: The frequency and severity of pedicle screw perforation were lower for iSV registration compared with StealthStation (97% versus 68% with Grade 0 medial perforation for iSV and StealthStation, respectively). Severe perforation occurred only with StealthStation (18% versus 0% for iSV). The overall time required for iSV registration (computational efficiency) was ∼10 to 15 minutes and was comparable with StealthStation registration (∼10 min). The mean target registration error was smaller for iSV relative to StealthStation (2.81 ± 0.91 versus 8.37 ± 1.76 mm). Conclusions: Pedicle screw placement was more accurate with iSV registration compared with state-of-the-art commercial navigation based on preoperative CT when alignment of the spine changed during surgery. Clinical Relevance: The iSV system compensated for intervertebral motion, which obviated the need for repeated vertebral registration while providing efficient, accurate, radiation-free navigation during open spinal surgery.